A Study on “Attitude and Acceptance of Fortified Foods in Urban Areas” - Shivani Singh, Divya Chandel (Indian Journal of Extension Education, 2018)
Food fortification is the addition of one or more essential nutrients to a food whether or not it is normally contained in the food, for the purpose of preventing or correcting a demonstrated deficiency of one or more nutrients in the population or specific population groups. Food fortification is the practice of deliberately increasing content of an essential micro nutrient in a food, so as to improvise the nutritional quality of the food supply and provide a public health benefit with minimal risk to health. The fortified market today largely consists of health food drinks, iodized salt, iron fortified biscuits and fortified edible oils. Health food drinks have been focused on general nutritional needs of growing children while iodized salt and iron- fortified biscuits have become mass product segments driven by nutrient deficiencies and support through various government policies. Some of the major companies operating in the global market for vitamin fortified and mineral enriched foods and beverages include The Pepsico Company, Mother Dairy, Quaker, Kellogg Company and The Proctor & Gamble Company and so on. The present study entitled “Attitude and acceptance of fortified foods in urban areas, a study – is a case study of Delhi/National Capital Region (NCR) metro consumers” that scatters light on the buyer’s preferences towards fortified foods.